2013
DOI: 10.3390/biom3010168
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Hydrophobic Protein Response to External Electric Field: A Molecular Modeling Approach

Abstract: The molecular dynamic (MD) modeling approach was applied to evaluate the effect of an external electric field on soybean hydrophobic protein and surface properties. Nominal electric field strengths of 0.002 V/nm and 0.004 V/nm had no major effect on the structure and surface properties of the protein isolate but the higher electric field strength of 3 V/nm significantly affected the protein conformation and solvent accessible surface area. The response of protein isolate to various external field stresses demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 20 publications
3
56
0
Order By: Relevance
“…The RMSD is calculated by evaluating the changes in the structure with a reference molecule that is normally the control (not under any external stress) (Budi, Legge, Treutlein, & Yarovsky, 2004). RMSD of the protein can be represented using the following equation (Singh et al, 2013b):…”
Section: Root Mean Square Deviation (Rmsd)mentioning
confidence: 99%
See 3 more Smart Citations
“…The RMSD is calculated by evaluating the changes in the structure with a reference molecule that is normally the control (not under any external stress) (Budi, Legge, Treutlein, & Yarovsky, 2004). RMSD of the protein can be represented using the following equation (Singh et al, 2013b):…”
Section: Root Mean Square Deviation (Rmsd)mentioning
confidence: 99%
“…It is well known that during processing food components undergo several chemical and physical changes; hence protein subjected to external stresses such as thermal, chemical and electrical stresses may lead to conformational changes to the molecular structure (Singh, Orsat, & Raghavan, 2013b). The functional properties of proteins depend on their structure and any change in it may alter the functionality (Singh, Munshi, & Raghavan, 2013a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, an order is created as the protein dries and the entropy of the protein molecules reduces (Xue et al, 1999). Singh et al (2013b) reported that under the effect of the nominal electric field strength of 0.002 V/nm and 0.004 V/nm, soybean hydrophobic protein reoriented itself in the direction of the electric field; additionally no considerable effect was observed on the secondary structure and surface properties of the protein. However, under an electric field strength of 3 V/nm, the protein unfolded and nearly all the helical structures were damaged.…”
Section: Enthalpy Changes ( H) Of Dsc Thermograms Over Amentioning
confidence: 99%